Information for contributors and readers for issue 3-2016 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2016)
CEON has marked The Military Technical Courier with “kk (quality control)” for the fourth year in a row The Center for Evaluation in Education and Science (CEON, http://ceon.rs/index.php/en/), publisher of the Serbian Citation Index (http://scindeks.ceon.rs/default.aspx?lang=en), published the Bibliometric Report on Scientific Journals for year 2015. In compliance with established practice, the relevant ministry in the government of the Republic of Serbia was notified so that the results could be dealt with in accordance with the Regulation on Validation, i.e. so that national journals could be classified for 2016.The Bibliometric Report for 2015 is of cumulative nature, encompassing the data from 2002 to the present. In this year’s Bibliometric Report, as well as in its 2012, 2013 and 2014 Reports, the CEON marked The Military Technical Courier with “kk (quality control through the CEON Aseestant system)” which represents the controlled quality of a journal in this evaluation system. The Military Technical Courier is one of the first journals in the Serbian Citation Index to obtain it.